Haloperidol- Induced Cardiopulmonary Arrest: A Case Report - Mermi, Osman; Ozer, Omer; Baykara, Sema; Atmaca, Murad (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2016)
Haloperidol is an antipsychotic which is widely used in emergency and psychiatry units. Sometimes, it is encountered some serious complications associated with haloperidol use, particularly haloperidol induced cardiac ones. In literature, life-threatening arrhythmias have been reported as case reports. Here, we report a case who had haloperidol-induced cardiopulmonary arrest.
Keywords: haloperidol; cardiopulmonary arrest; side effect